Determinant Model of Employee Performance through Job Satisfaction from a Human Resource Management Perspective at an Umrah Travel Agency - Kamsariaty Kamsariaty; Ryan Firdiansyah Suryawan; Suhartini Suhartini; Monizaihasra Mohamed; Hadiansyah Hadiansyah (Greenation International Journal of Economics and Accounting, 2026)
The Umrah travel agency sector in Indonesia has experienced significant growth, yet this is often not accompanied by an improvement in the organization’s internal performance. Suboptimal employee performance is influenced by low organizational support, weak work discipline, and an unsatisfactory compensation system. This study aims to analyze the influence of organizational support, work discipline, and compensation on employee performance, with job satisfaction as the mediating variable. The approach used is quantitative with an explanatory design, involving 101 respondents who are employees of Umrah travel agencies in Lampung Province, selected through purposive sampling. Hypothesis testing was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 3.0 software. The analysis results indicate that organizational support, work discipline, and compensation have a positive and significant effect on job satisfaction. However, directly, only compensation has a significant effect on employee performance, while organizational support and work discipline do not have a direct effect. Job satisfaction was found to act as a crucial mediating variable; it fully mediates the effects of organizational support and work discipline on performance, and partially mediates the effect of compensation on performance. These findings imply that the psychological factor of job satisfaction serves as the primary bridge in translating human resource management practices into improved employee performance in the religious services sector.